2015
DOI: 10.3390/ijms16022530
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Inhibits Proliferation, Invasiveness and Tumor Growth by Up-Regulation of Adhesion Molecules, Suppression of Gelatinases Activity, and Induction of Apoptosis in Nasopharyngeal Carcinoma Cells

Abstract: (−)-Epigallocatechin-3-gallate (EGCG), a major green tea polyphenol, has been shown to inhibit the proliferation of a variety of tumor cells. Epidemiological studies have shown that drinking green tea can reduce the incidence of nasopharyngeal carcinoma (NPC), yet the underlying mechanism is not well understood. In this study, the inhibitory effect of EGCG was tested on a set of Epstein Barr virus-negative and -positive NPC cell lines. Treatment with EGCG inhibited the proliferation of NPC cells but did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 69 publications
4
55
0
4
Order By: Relevance
“…The role of Sp1 in apoptosis has been well documented in a number of cancer cells, including nasopharyngeal carcinoma [37,38] . Interestingly, a recent study by Yang et al found that downregulated expression of Sp1 was associated with induction of autophagy in the human myeloid leukemia cell line K-562 [39] .…”
Section: Suppression Of Sp1 Is Involved In Physcion-induced Apoptosismentioning
confidence: 99%
“…The role of Sp1 in apoptosis has been well documented in a number of cancer cells, including nasopharyngeal carcinoma [37,38] . Interestingly, a recent study by Yang et al found that downregulated expression of Sp1 was associated with induction of autophagy in the human myeloid leukemia cell line K-562 [39] .…”
Section: Suppression Of Sp1 Is Involved In Physcion-induced Apoptosismentioning
confidence: 99%
“…One of the disadvantages of the 3D spheroid model is the lack of tumor complexity, which can be overcome by the increase in the range and convolution of models applicable to researchers including co-culture system and patient-derived spheroids (67,68). Although we have the capability to recreate the tumor microenvironment architecture with a matrix of the 3D cell culture, variability in the matrix, particularly ones that are biologically derived, may yield non-reproducible results.…”
Section: D Spheroid Modelsmentioning
confidence: 99%
“…A number of previous studies have developed improved NPC models based on spheroid cultures; these have increased in number due to novel culture methods emerging from the field of tissue engineering (Table I) (8,42,43,67,. Formerly, the utilization of ultra-low attachment plates and hanging drop were the most common methods used to generate spheroids from NPC cells (74).…”
Section: Npc 3d Spheroidsmentioning
confidence: 99%
“…A EGCG, uma das catequinas isoladas e purificadas a partir do chá-verde, avaliada no presente estudo, tornou-se uma das substâncias naturais mais estudadas atualmente, sendo a principal responsável pelos efeitos biológicos que resultam na prevenção e tratamento de diferentes doenças (Yun et al, 2007;Yang et al, 2010;Hodgson e Croft, 2010;Prabhakar et al, 2010;Rao e Pagidas, 2010;Yang e Wang, 2010;Rodriguez et al, 2011;Subramaniam et al, 2012;Jung et al, 2012;Cai et al, 2013;Wierzejska, 2014;Fang et al, 2015;Tenore et al, 2015).…”
Section: Discussão 5 Discussãounclassified
“…O chá verde é uma das bebidas mais populares em todo o mundo e tem recebido atenção especial por apresentar comprovados efeitos na saúde geral (Chung et al, 2001;Pianetti et al, 2002;Chung et al, 2003;Dreger et al, 2008;Lee et al, 2009;Hodgson e Croft, 2010;Prabhakar et al, 2010;Rao e Pagidas, 2010;Yang e Wang, 2010;Subramaniam et al, 2012;Jung et al, 2012;Cai et al, 2013;Wierzejska, 2014;Fang et al, 2015;Tenore et al, 2015). Seus principais componentes químicos são flavonóides e catequinas, que correspondem a aproximadamente 26,7% do seu conteúdo.…”
Section: Introductionunclassified